Economic Empowerment of Islamic Boarding Schools in Realizing SustainableDevelopment Goals (SDGs) in the Era of Society 5.0at Lirboyo Islamic Boarding School Kediri - Rahmad Ikbal Devid (MONETARIUM: Journal of Economics Business and Management, 2024)
This article explains what the Lirboyo Islamic boarding school is doing for its students in the era of society 5.0. namely empowerment through increasing the economic and entrepreneurial competence of the students with supporting factors including the fulfillment of the students' needs, the existence of human resources (HR) both leaders and staff, the system in place, the attitude of the community and the sincere and sincere intentions of the administrators and managers. The method used is a qualitative method with descriptive research type. The data taken is written or verbal data as well as natural behavior. The data sources in this research use, 1) primary data, obtained through interviews with informants in the field where the research was conducted, 2) secondary data, obtained from books, articles, journals, the internet which have been arranged regularly. Data collection techniques in research use interview techniques, observation and documentation studies. The results of this research show that Islamic boarding schools are Islamic educational institutions that have great potential in empowering students in the economic sector through BUMPs in Islamic boarding schools. The empowerment carried out by Islamic boarding schools for their students is empowerment through increasing the economic competence of the students so that later, when the students return to their community, they can become role models either in the productive economic sector or as cadres of economic empowerment , in addition to their main role as ustadz/ustadzah. who has abilities in the field of Islamic religious knowledge.